Acceptance and determinants of indoor residual spraying in two blocks of Tripura: using LQAS technique - Debnath, Sankha Subhra; Baidya, Subrata; Das, Rituparna; Deb, Durba (International Journal Of Community Medicine And Public Health, 2020)
Background: Indoor Residual Spray (IRS) with insecticide (DDT) is one of the most important component of integrated vector management for malaria prevention. Though, NVBDCP targets at least 80% coverage at high risk malaria zone by effective protective measures (eg. IRS) by 2017, but the real coverage is however limited, due to low community acceptance and several other factors. Objectives were to assess the IRS coverage in two blocks of Tripura and to study the factors influencing IRS acceptance. Methods: A cross sectional study was conducted among 600 households of all 30 sub centres of two blocks of Sepahijala district of Tripura 2015 to 2017 using LQAS technique. Head of the families were interviewed to collect information regarding IRS. Data analysis was done in SPSS 20.0. Statistical analysis used Chi square test was applied to assess the association between different variables. P-value (<0.05) was considered as statistically significant. Results: IRS coverage and acceptance were 61.7% and 75.05% respectively. The factors influencing IRS acceptance were Age of the Head of the family p 0.015, Religion p 0.011, Education p 0.04, Occupation p 0.018, type of Community p.0.000, House type p 0.000, By LQAS analysis, 9 out of 30 lots were accepted for having target coverage of IRS (80%). Conclusions: IRS coverage was lower than the NVBDCP target of 80 % coverage. Sound programmatic management strategy along with IEC, BCC is needed to scale up the coverage.